Magnetoresistance metrology of skyrmion hosting multilayer thin films - Lew, Lincoln Wai Cheong (2017)
In this magnetoresistance metrology study, the main goal is to establish the detection of room temperature skyrmions at low current, so that skyrmions stays fixed, with an effectively and reliable method. In addition to it, is the identification of the critical current that will allow skyrmions motion via electrical pulsing. These are the crucial steps that we are undertaking to allow us to conduct dynamic detection of skyrmions, which in this case skyrmions are moving. The key findings of this study have been exciting because it has shown the reproducibility of skyrmions detection in both thin films and Hall bars. Furthermore, the transport measurement proves to be a success even in the unprecedented measurement of other different material composition, having a metal oxide layer. Lastly, we have successfully identified the minimum current required to allow observable skyrmion motion. These key findings are crucial as they allow us to establish towards the next research goal of electrical detection of moving skyrmions.